MicroRNA and mesial temporal lobe epilepsy with hippocampal sclerosis: Whole miRNome profiling of human hippocampus. (16th August 2017) - Bencurova, Petra; Baloun, Jiri; Musilova, Katerina; Radova, Lenka; Tichy, Boris; Pail, Martin; Zeman, Martin; Brichtova, Eva; Hermanova, Marketa; Pospisilova, Sarka; Mraz, Marek; Brazdil, Milan
Summary: Objective: Mesial temporal lobe epilepsy (mTLE) is a severe neurological disorder characterized by recurrent seizures. mTLE is frequently accompanied by neurodegeneration in the hippocampus resulting in hippocampal sclerosis (HS), the most common morphological correlate of drug resistance in mTLE patients. Incomplete knowledge of pathological changes in mTLE+HS complicates its therapy. The pathological mechanism underlying mTLE+HS may involve abnormal gene expression regulation, including posttranscriptional networks involving microRNAs (miRNAs). miRNA expression deregulation has been reported in various disorders, including epilepsy. However, the miRNA profile of mTLE+HS is not completely known and needs to be addressed. Methods: Here, we have focused on hippocampal miRNA profiling in 33 mTLE+HS patients and nine postmortem controls to reveal abnormally expressed miRNAs. In this study, we significantly reduced technology‐related bias (the most common source of false positivity in miRNA profiling data) by combining two different miRNA profiling methods, namely next generation sequencing and miRNA‐specific quantitative real‐time polymerase chain reaction. Results: These methods combined have identified and validated 20 miRNAs with altered expression in the human epileptic hippocampus; 19 miRNAs were up‐regulated and one down‐regulated in mTLE+HS patients. Nine of these miRNAs have not been previously associated with epilepsy, and 19 aberrantly expressed miRNAs potentially regulate the targets and pathways linked with epilepsy (such as potassium channels, γ‐aminobutyric acid, neurotrophin signaling, and axon guidance). Significance: This study extends current knowledge of miRNA‐mediated gene expression regulation in mTLE+HS by identifying miRNAs with altered expression in mTLE+HS, including nine novel abnormally expressed miRNAs and their putative targets. These observations further encourage the potential of microRNA‐based biomarkers or therapies.